2022
DOI: 10.3390/ijerph192114620
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Capacitive-Resistive Electric Transfer on Sports Performance in Paralympic Swimmers: A Stopped Randomized Clinical Trial

Abstract: Throughout history a variety of therapeutic tools have been studied as possible enhancers of sports activities. This study proposes the use of Capacitive-Resistive Electric Transfer (CRET) as a performance booster to paralympic athletes, specifically those belonging to the Spanish Paralympic swimming committee. The study was a randomized, single-blind, and observer-blind, crossover clinical trial. Six athletes were randomly assigned to three groups: one treated with CRET (A); a placebo group (B) and a control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 61 publications
0
0
0
Order By: Relevance
“…In the study by Duñabeitia [37] found that biomechanical parameters (step length, step frequency, step height and step angle) improved more quickly with Tecartherapy than with passive rest after an exhaustive training session. On the other hand, in the study by De Sousa-De Sousa [38] the use of Tecartherapy before pre-competition did not result in an improvement in the athletes' performance. Suggesting that increased blood flow improves muscle recovery and not muscle performance.…”
Section: Discussionmentioning
confidence: 67%
“…In the study by Duñabeitia [37] found that biomechanical parameters (step length, step frequency, step height and step angle) improved more quickly with Tecartherapy than with passive rest after an exhaustive training session. On the other hand, in the study by De Sousa-De Sousa [38] the use of Tecartherapy before pre-competition did not result in an improvement in the athletes' performance. Suggesting that increased blood flow improves muscle recovery and not muscle performance.…”
Section: Discussionmentioning
confidence: 67%